2018
DOI: 10.7456/1080sse/127
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Non-Technical Skills Development Among Engineering Students: An Employers’ Perspective

Abstract: Many complaints come from employers regarding on non-technical skills among engineering graduates. Non-technical skills can be effectively developed during industrial training while they are still undergraduates. This paper is presenting the perspective of employers on factors that are developing the non-technical skills during industrial training. A qualitative study was done by interviewing five employers from electrical and electronics industries to gain the data. Thematic analysis was done after transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…According to Azmi et al [30], the length of six months is the optimal period for an undergraduate to learn technical and non-technical skills and to gain work experience. Azmi et al [28] found that employers prefer the period of six months for engineering students in order for them to identify, study, comprehend, and employ the skills learned during the internship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Azmi et al [30], the length of six months is the optimal period for an undergraduate to learn technical and non-technical skills and to gain work experience. Azmi et al [28] found that employers prefer the period of six months for engineering students in order for them to identify, study, comprehend, and employ the skills learned during the internship.…”
Section: Discussionmentioning
confidence: 99%
“…Tymon [18] addressed the matter through the students' perspectives on employability and found that there was limited alignment between students' and stakeholders' views. Some studies, in addition, addressed the students' satisfaction with the internship experience [19][20][21][22][23][24][25][26][27][28][29] and suggested measures to improve internship effectiveness, namely, clarification of tasks, communication, and expectations on challenging assignments to be completed in reasonable time [30], together with feedback and mentoring [31].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the existing industrial training program has some drawbacks, including insufficient documentation, a lack of industrial training procedures and guidelines, a lack of recorded industrial training syllabus and standards of practice, and a lack of defined goals and curricular structure. In addition, existence of a gap in students' industrial training diagnostic, formative, and summative assessments; learning outcomes after completion of training; and host company supervisor competency in implementing industrial training and training engineering students [3]; which shows almost the same outcome according to the research conducted by [4] after five years. This illustrates that changes made to correct the enhancement of non-technical skills through industrial training still do not resolve the real root cause and still have a discrepancy in what we have developed and what the employer wants.…”
Section: Introductionmentioning
confidence: 99%